Handwashing Ability Assessment for Students with Intellectual Barriers - Asep Rudi Irawan (Universitas Pendidikan Indonesia (UPI), 2021)
This study aimed to determine the assessment of the ability to wash hands for students with intellectual disabilities. We used a qualitative method with literature study activities and field studies (interviews, observations, and documentation). The results showed that the assessment of the ability to wash hands for students with intellectual disabilities was carried out in stages, namely making assessment instruments, determining subjects, preparing the necessary equipment, conducting assessments, and analyzing data from the assessment results. The activity of assessing the ability to wash hands for students with intellectual disabilities has the aim of knowing the weaknesses, strengths, and potential of students in the ability to wash hands. It is hoped that the results of this assessment can be used as a basis for making hand-washing learning programs for students with special needs, especially students with intellectual disabilities.